POST-COVID-19 SYNDROME IMAGING FINDINGS IN SEVERE COVID-19 WITH PULMONARY CAVITATION: A CASE REPORT - Soekardi, Adi; Suryamin, Ricky (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2024)
In the fourth year of the SARS-CoV-2 pandemic, there is corresponding increase in the proportion exhibiting long-term symptoms and chronic respiratory complication associated with the disease. The British Medical Journal consider post-COVID syndrome as to symptoms continuing for more than 12 weeks. The most prevalent findings were "ground glass opacity" and "fibrotic-like changes”. The term "fibrotic-like changes" exhibited variations across studies, encompassing architectural distortion with traction bronchiectasis, honeycombing, or both, as well as traction bronchiectasis/bronchiolectasis, volume loss, or both. Other descriptions included evidence of stripe-like fibrosis without reticular opacity and the presence of honeycombing, reticulation, and traction bronchiectasis. Bronchial abnormalities, such as wall thickening and dilation, are frequently observed in patients during the acute and early convalescent phases of COVID-19 pneumonia, but their frequency and severity tend to decrease over time.1 However, in a subset of patients, bronchial dilation continues to persist even after recovery from COVID-19 pneumonia. Pulmonary cavitary lesions are uncommon occurrences in cases of COVID-19 pneumonia. Based on a case series, it has been found that approximately 3% of patients who develop COVID-19 pneumonia experience this complication. Despite ongoing research, the exact mechanisms behind the development of pulmonary cavitary lesions in COVID-19 remain unknown. At present, there is no single effective treatment for long COVID. However, low-dose naltrexone, β-blockers, and intravenous immunoglobulin can be considered for treating different symptoms and conditions.